2020
DOI: 10.3390/cells9040944
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium avium subsp. paratuberculosis MAP1889c Protein Induces Maturation of Dendritic Cells and Drives Th2-Biased Immune Responses

Abstract: Mycobacterium avium subsp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Purified Rv2145c was not cytotoxic in bone marrow-derived macrophages (BMDMs) up to a concentration of 10 μg/ml ( Figure 1B ). We previously reported that MAP1889c, which is homologous with Rv2145c, stimulates DCs and macrophages to increase surface molecule presentation and secrete cytokines ( 23 ). Therefore, we investigated whether Rv2145c could also induce macrophage activation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Purified Rv2145c was not cytotoxic in bone marrow-derived macrophages (BMDMs) up to a concentration of 10 μg/ml ( Figure 1B ). We previously reported that MAP1889c, which is homologous with Rv2145c, stimulates DCs and macrophages to increase surface molecule presentation and secrete cytokines ( 23 ). Therefore, we investigated whether Rv2145c could also induce macrophage activation.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that Mycobacterium avium subsp. paratuberculosis MAP1889c, which has homology with Rv2145c, induces DC maturation and Th2 responses and promotes Mycobacterium avium growth and IL-10 production in macrophages ( 23 ). In the present study, Rv2145c induced macrophage activation with elevated IL-10 production ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NOD2 further stimulates the transcription factor NF-KB that regulates pro-inflammatory cytokine expression (168). The TLR1, TLR2, and TLR4 genes also code for PRRs that recognize MAP-associated membrane patterns and initiate the host innate and adaptive immune responses in the infected host (169)(170)(171). Another PRR coded by CLEC7A is expressed on antigen presenting cells (APCs) and is known to recognize MAP and initiate cytokine secretion by phagocytic cells through its synergistic action with TLR2 and TLR4 receptors (169).…”
Section: Genomic Studies Related To Johne's Diseasementioning
confidence: 99%